Formulasi dan Uji Aktivitas Antioksidan Blush Powder Ekstrak Beras Merah (Oryza nivara L.) Dengan Metode DPPH - Elsa Marliyanti; Salsabila Adlina; Nitya Nurul Fadilah (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Red rice (Oryza nivara L.) contains anthocyanin pigments which are a group of flavonoids that act as natural dyes and contain antioxidants. The aim of this research is to formulate red rice into blush powder preparations in 3 different concentrations, namely 10%, 20% and 30%, and test the antioxidant activity. This study uses an experimental method. Manufacture of preparations, evaluation of preparations and test of antioxidant activity. The physical blush powder evaluation results met the requirements including organoleptic tests, homogeneity tests and pH tests. However, there was a change in the color of the preparation during the stability test using the cycling test method on F2 and F3. The strongest antioxidant activity test was found in formula 1 (10%) with an IC50 value of 74.52 ppm in the strong category.